Indole-Acetic Acid Promotes Ammonia Removal Through Heterotrophic Nitrification, Aerobic Denitrification With Mixed Enterobacter sp. Z1 and Klebsiella sp. Z2 - Zhang, Yuxiao; Xu, Qing; Wang, Gejiao; Shi, Kaixiang (Frontiers in Microbiology, 2022)
Mixed Enterobacter sp. Z1 and Klebsiella sp. Z2 displayed an outstanding ammonia removal capacity than using a single strain. Metabolomics, proteomics, and RNA interference analysis demonstrated that the HNAD process was closely related to indole-acetic acid (IAA). Under the cocultured conditions, the excess IAA produced by Z2 could be absorbed by Z1 to compensate for the deficiency of IAA in the cells. IAA directly induced the expression of denitrifying enzymes and further activated the IAA metabolism level, thus greatly improving the nitrogen removal ability of Z1. In turn, nitrate and nitrite induced the expression of key enzymes in the IAA pathways. Moreover, Z1 and Z2 enhanced two IAA metabolic pathways in the process of mixed removal process. The activated hydrolysis-redox pathway in Z1 reduced the oxidative stress level, and the activated decarboxylation pathway in Z2 promoted intracellular energy metabolism, which indirectly promoted the process of HNAD in the system.